Effect of using Problem-Based Learning on the Academic Achievement of Higher Secondary School Students - Tshewang Dorji (International Journal of Asian Education, 2021)
The quasi-experimental study examines the effect of the Problem-based Learning (PBL) teaching strategy on one higher secondary school student's academic achievement under Thimphu Thromde, Bhutan. The student participants were selected through non-probability convenient sampling techniques. All students of XI Arts (N=30) and XI Commerce (N=38) participated in the study. Class XI Arts students were used as a controlled group and XI Commerce students as an experimental group. The experimental group was taught using PBL, and the control group was taught using the traditional lecture method. The pre-test data were collected through class test 1, and post-test data were collected through class test 2 and 5 points Likert scale survey questionnaire. The results revealed that the experimental group scored higher marks in the class test than the control group. The mean score of the pre-test of the XI Arts and XI Commerce (both controlled group) were 40.75 and 38.81 initially. The mean score of the experiment group's post-test showed 44.73, while the controlled group managed only 43.00. Further, the experimental group had a favorable opinion on the effectiveness of the PBL strategy. The study recommends the implementation of the PBL teaching strategy despite PBL being time-consuming and resource-intensive.